al-Makhṭūṭ fī Manṭiqat Wādī Mīzāb: Qīmatuhu al-Ḥaḍāriyya wa’l-Tārīkhiyya min khilāl Maktabat al-Shaykh al-Ḥājj Ṣāliḥ b. ʿUmar Laʿlī (1287-1347/1870-1928) - Ḥammūda, Muṣṭafà b. al-Ḥājj Bakīr (2003)
A statistical study of one of the most important libraries in Mīzāb (1210 MSS). An inventory of this library was completed in Sept. 2000, as tenth in a series of inventories of MSS in libraries in Wādī Mīzāb (Dalīl Makhṭūṭāt Wādī Mīzāb). Of the following libraries that are (more or less) accessible for researchers the inventories are not yet finished [at the time of writing this paper]: Makt. al-Shaykh Ḥammū Bābā Umūsà, Makt. Maʿhad ʿAmmī Saʿīd and Makt. al-Ḥājj Masʿūd Bābakr al-Ghardāwī, all three in Ghardaïa; Makt. al-Quṭb al-Shaykh Iṭfayyish, Makt. al-Istiqāma, Makt. al-Ḥājj Ibr. Ūzikrī, all in Beni Isguen; Makt. al-Salaf in Melika; Makt. al-Shaykh Bālḥājj in Guerara; Makt. al-Nahḍa in El Ateuf.
Keywords: Manuscrits – Mzab